Efficacy of cosmetic products in cellulite reduction: systematic review and meta‐analysis. (14th June 2013) - Turati, F.; Pelucchi, C.; Marzatico, F.; Ferraroni, M.; Decarli, A.; Gallus, S.; La Vecchia, C.; Galeone, C.
Abstract Background The number of original articles investigating the efficacy of cosmetic products in cellulite reduction increased rapidly in the last decade; however, to our knowledge, no systematic review and meta‐analysis has been performed so far. Objective We conducted a systematic review of in vivo studies on humans adopting the PRISMA guidelines. Moreover, we used a meta‐analytic approach to estimate the overall effect of cosmetic creams in cellulite treatment from controlled trials with more than 10 patients per arm, using thigh circumference reduction as the outcome measure. Methods Medline and Embase were searched up to August 2012 to identify eligible studies. Results Twenty‐one original studies were included in the present systematic review. All studies were clinical trials, most of them recruited women only and 67% had an intra‐patient study design. About half of the active cosmetic creams tested only contained one active ingredient among xanthenes, herbals or retinoids. The other studies tested cosmetic creams with more complex formulations and most of them included xanthenes. A total of seven controlled trials satisfied the inclusion criteria for the meta‐analysis. The pooled mean difference of thigh circumference reduction between the treated and the controlled group was −0.46 cm (95% confidence intervals, CI: −0.85, −0.08), with significant heterogeneity between studies (P < 0.001). Conclusion This article provides a systematic evaluation of the scientific evidence of the efficacy of cosmetic products in cellulite reduction and supports a moderate efficacy in thigh circumference reduction.